Direct Participation of Solvent Molecules in the Formation of Supramolecular Polymers. Issue 39 (25th May 2022) - Ghosh, Goutam; Chakraborty, Anwesha; Pal, Prasun; Jana, Biman; Ghosh, Suhrit
Abstract: This article reports supramolecular polymerization of two bis‐amide functionalized naphthalene‐diimide (NDI) building blocks (NDI−L and NDI−C) in two solvents, namely n ‐heptane (Hep) and methylcyclohexane (MCH). NDI−L and NDI−C differ only by the peripheral hydrocarbon wedges, consisting of linear C7 chains or cyclic methylcyclohexane rings, respectively. UV/Vis and FTIR spectroscopy studies reveal distinct internal order and H‐bonding pattern for NDI−L and NDI−C aggregates irrespective of the solvent system, indicating the dominant role of the intrinsic packing parameters of the individual building block, possibly influenced by the peripheral steric crowding. However, NDI−L produces a significantly stronger gel in Hep compared to MCH as evident from the rheological and thermal properties. In contrast, NDI−C exhibits a clear preference for MCH, producing gel with moderate strength but in Hep it fails to produce 1D morphology or gelation. All‐atom molecular dynamics (MD) simulation studies corroborate with the experimental observation and provide the rationale for the observed solvent‐shape effect by revealing a quantitative estimate regarding the thermodynamics of self‐assembly in these four combinations. Such clear‐cut shape‐matching effect (between the peripheral hydrocarbon wedge and the solvent system) unambiguously support a direct participation of the solvent molecules during supramolecular polymerization and presence of a closely‐adhered solvent shell around the supramolecular polymers, similar to the first layer of water molecules around the protein surface. Solvent induced CD experiments support this hypothesis as induced CD band was observed only from a chiral co‐solvent of matching shape. This is reconfirmed by the higher de‐solvation temperature of the shape‐matching NDI/solvent system combination compared to the shape mis‐match combination in variable temperature UV/Vis experiments, revealing transformation to a different aggregate at higher temperatures rather than disassembly to the monomer for all four combinations. Abstract : Shape‐matching between the peripheral hydrocarbon wedges and hydrocarbon solvent molecules regulates supramolecular polymerization and gelation. Such non‐trivial solvent effect strongly evokes the possibility of direct participation of solvent molecules in the nucleation by shape‐matching dependent van der Waals interaction and presence of a closely associates solvent shell around the supramolecular polymers similar to first layer of water molecules around the protein surface.